Tag der Freiheit - Unsere Wehrmacht Tag der Freiheit - Unsere Wehrmacht Tag der Freiheit - Unsere Wehrmacht Tag der Freiheit - Unsere Wehrmacht . Day of Freedom - Our Armed Forces - Riefenstahl, Leni (Germany, 1935)
The 7th Nazi Party Congress with glorious marching of German troops during the colorful ceremonies in Nuremberg on German Armed Forces Day 1935.